The role of creativity in principals’ leadership practices towards parental involvement The mediating role of school practices and school climate - Keetanjaly, A.; Abdul Kadir, Suhaida; Luan, Wong Su; Arnida Abdullah, Arnida (Emerald, 2019)
Purpose–The involvement of parents in schools and their contribution towards their children’s academic learning have been a focal point in educational research. The purpose of this paper is to identify the factors that influence parental involvement in secondary schools and subsequently proposed a comprehensive parental involvement model. Design/methodology/approach–Research articles, reports and dissertations on the factors that influence parental involvement were reviewed to obtain related empirical evidence for the development of a workable model. Findings–A conceptual framework was proposed to understand the factors that influence parental involvement. The role of creativity in principals ’leadership practices and parental involvement in secondary schools were found to be related. Additionally, this relationship was found to be mediated by school practices and school climate. Research limitations/implications–A framework on the factors that influence parental involvement guided by literature review and three main hypotheses for testing were proposed, which require further empirical assessment. Practical implications–The school–parent partnership shares a common understanding of the educational needs and social development of the children. The school administrators, school community,stakeholders and related policymakers can effectively leverage the findings of this study in the effort to enhance parental involvement within the school context. Originality/value–Only a handful of research-based studies probed into the factors that influence parental involvement in secondary schools within the Malaysian context. This study identified several significant factors that enhance parental involvement in secondary schools.